Chlorine disinfection of dye wastewater: Implications for a commercial azo dye mixture - Vacchi, Francine Inforçato; Albuquerque, Anjaina Fernandes; Vendemiatti, Josiane Aparecida; Morales, Daniel Alexandre; Ormond, Alexandra B.; Freeman, Harold S.; Zocolo, Guilherme Julião [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Umbuzeiro, Gisela (Elsevier, 2013)
Azo dyes, the most widely used family of synthetic dyes, are often employed as colorants in areas such as textiles, plastics, foods/drugs/cosmetics, and electronics. Following their use in industrial applications, azo dyes have been found in effluents and various receiving waters. Chemical treatment of effluents containing azo dyes includes disinfection using chlorine, which can generate compounds of varying eco/genotoxicity. Among the widely known commercial azo dyes for synthetic fibers is C.I. Disperse Red 1. While this dye is known to exist as a complex mixture, reports of eco/genotoxicity involve the purified form. Bearing in mind the potential for adverse synergistic effects arising from exposures to chemical mixtures, the aim of the present study was to characterize the components of commercial Disperse Red 1 and its chlorine-mediated decoloration products and to evaluate their ecotoxicity and mutagenicity. In conducting the present study, Disperse Red 1 was treated with chlorine gas, and the solution obtained was analyzed with the aid of LC-ESI-MS/MS to identify the components present, and then evaluated for ecotoxicity and mutagenicity, using Daphnia similis and Salmonella/microsome assays, respectively. The results of this study indicated that chlorination of Disperse Red 1 produced four chlorinated aromatic compounds as the main products and that the degradation products were more ecotoxic than the parent dye. These results suggest that a disinfection process using chlorine should be avoided for effluents containing hydrophobic azo dyes such commercial Disperse Red 1. © 2012 Elsevier B.V..
Keywords: C.I. Disperse Red 1; Chlorination; Commercial dye mixture; Daphnia; LC-MS; Salmonella/microsome assay; Chemical mixtures; Chemical treatments; Chlorinated aromatic compounds; Chlorine disinfection; Chlorine gas; Complex mixture; Daphnia similis; Decoloration; Degradation products; Disinfection process; Disperse red 1; Dye wastewaters; Ecotoxicity; LC-ESI-MS/MS; Mutagenicity; Receiving waters; Synergistic effect; Synthetic dyes; Assays; Azo dyes; Chlorine; Chlorine compounds; Degradation; Disinfection; Industrial applications; Mixtures; Synthetic fibers; Wastewater treatment; Water pollution control; Effluents; aromatic compound; azo dye; chlorine; n ethyl n (2 hydroxyethyl) 4 (4 nitrophenylazo); unclassified drug; azo compound; coloring agent; disperse red 1; chlorination; disinfection; dye; effluent; wastewater; ecotoxicology; genotoxicity; hydrophobicity; chemical analysis; chemical composition; chemical reaction; concentration response; controlled study; degradation; dye waste water; ecotoxicity; electrospray mass spectrometry; environmental impact; industrial waste; liquid chromatography; microsome; mutagenicity; nonhuman; priority journal; Salmonella; toxicity testing; waste water; waste water management; animal; chemistry; drug effect; high performance liquid chromatography; methodology; tandem mass spectrometry; water management; water pollutant; animal experiment; newborn; Animals; Azo Compounds; Chromatography, High Pressure Liquid; Coloring Agents; Spectrometry, Mass, Electrospray Ionization; Tandem Mass Spectrometry; Toxicity Tests, Acute; Waste Water; Water Pollutants, Chemical; Water Purification